2008
DOI: 10.1038/ijo.2008.216
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of interleukin-23/interleukin-17 proinflammatory axis in obese women

Abstract: Objective: To compare the concentrations of cytokines belonging to Th17 axis (interleukin (IL)-17 and IL-23) and Th1 axis (IL-12 and interferon (IFN)-g) in obese and lean women, and to investigate their relationships with the proinflammatory adipokine leptin, proinflammatory cytokine macrophage migration inhibitory factor (MIF) and anthropometric and metabolic parameters of obesity. Design: Cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
187
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(214 citation statements)
references
References 39 publications
12
187
2
3
Order By: Relevance
“…DIO is reversible and it should be interesting to assess, to what extent and at which disease stage weight loss can reduce Th17 expansion and disease exacerbation, information that might have clinical impact. While this present manuscript was in submission, first observations from a small clinical study demonstrated elevated IL-17 serum levels in obese patients [21], suggesting that our observations in rodents are likely relevant to human disease. IL-6-dependent Th17 expansion is a clinically prominent element of pro-inflammatory diseases in obesity.…”
Section: Discussionmentioning
confidence: 72%
“…DIO is reversible and it should be interesting to assess, to what extent and at which disease stage weight loss can reduce Th17 expansion and disease exacerbation, information that might have clinical impact. While this present manuscript was in submission, first observations from a small clinical study demonstrated elevated IL-17 serum levels in obese patients [21], suggesting that our observations in rodents are likely relevant to human disease. IL-6-dependent Th17 expansion is a clinically prominent element of pro-inflammatory diseases in obesity.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, besides the classic proinflammatory cytokine TNF-a, the role of IL-17 in adipose tissue and fat metabolism has been drawing attention 53,54 . Clinical studies have demonstrated that obese women exhibit increased levels of circulating IL-23 and IL-17, suggesting a potential role for IL-17 in obesity 55 . As comparable to human studies, several animal experiments indicate that obesity promotes Th17 expansion and subsequent IL-17 production, exacerbating disease severity in murine models of multiple sclerosis and inflammatory bowel disease, both of which are representative Th17-related diseases as well as psoriasis 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decreased blood level of adiponectin in obesity also contributes to the action of the pathway as adiponectin can block insulin and leptin [Fujisawa et al, 2008;Huang and Chen, 2009a]. Recently, IL23/17 has also been shown to be activated in obesity which in turn activates the Src/PI3K/Akt pathway [Hsieh et al, 2002;Sumarac-Dumanovic et al, 2009].…”
Section: Activation Of the Src/pi3k/akt Signal Pathway In Obesitymentioning
confidence: 99%